A Comprehensive Review of Early Marriage in Indonesia - Dwi Utami (Proceedings Series on Social Sciences & Humanities, 2023)
Early marriage is a common social phenomenon in Indonesia that has significant impacts on individuals, families and communities. In addition, early marriage can hinder the physical, emotional and psychological development of adolescents as well as education and the economy. To overcome the problem of early marriage, it is important to understand the factors that influence it. Therefore, this study aims to analyze the factors that influence the occurrence of early marriage and efforts to reduce it. The research method used is normative juridical, namely with statutory documents and literature studies related to the research. The results show that there are several factors that influence the occurrence of early marriage. These factors include family factors, economic factors, cultural factors, educational factors and so on. These factors are interrelated and influence individual decisions in deciding to marry at a relatively young age. Therefore, it is necessary to make several efforts to reduce early marriage, such as increasing legal awareness, strengthening education, and developing policies that focus on the protection of children and adolescents.